Carbohydrate reserves on postharvest of lisianthus cut flowers - Cavasini, Raquel [UNESP]; Laschi, Denise [UNESP]; Tavares, Armando Reis; Lima, Giuseppina Pace Pereira [UNESP] (Lepidus Tecnologia, 2018)
Floriculture industry demands for products with high quality and durability; however, there is a lack of studies related to the postharvest physiology of cut flowers. We aimed to study phenolic contents of lisianthus (Eustoma grandiflorum) stems treated with ethylene inhibitors (1-Methylcyclopropene - 1-MCP and Salicylic Acid - SA) and different storage temperatures (room at 24 ± 2 °C and pre-exposure to the cold chamber at 9 ± 2 °C for 24 hours) during the post-harvest. Total soluble carbohydrate contents decreased during the experimentation, characterizing the consumption of the reserves during lisianthus post-harvest. The 1-MCP treatment slowed the decrease of total soluble carbohydrate contents. SA treatment had the lowest total soluble carbohydrate contents in both storage temperatures.
Keywords: Ethylene inibhitors; Eustoma grandiflorum; Salicilic acid; Sugar